Patient satisfaction and quality of care of the internal medicine service of Hospital Daniel Alcides Carrión. Huancayo - Perú: Satisfacción del usuario del servicio de medicina interna sobre la calidad de atención en el Hospital Daniel Alcides Carrión, Huancayo – Perú - Febres-Ramos, Richard J. (2020)
Introduction: Patient satisfaction is an indicator of the quality of care provided in health services.Knowing the level of satisfaction will improve deficiencies and reaffirm strengths to develop a healthsystem that provides the quality care that patients demand. Objective: To determine the satisfactionof the quality of service of patients of external Internal Medicine consultation of Hospital Daniel AlcidesCarrión - Huancayo, from July to November 2016. Methods: Observational, descriptive, cross-sectionalstudy. The sample consisted of 292 patients. The quality of service in the health system according topatient satisfaction was measured using the standardized SERVQUAL questionnaire. Results: 57% ofthe sample was female, the ages of the participants ranged from 36 to 45 years. Similarly, 36% of usershad complete secondary education and 63% were continuing patients. Overall satisfaction was 60.3%.The percentage values depended on the dimensions of safety and empathy with 86.8% and 80.3%satisfaction, respectively. The highest level of dissatisfaction was obtained by the dimension of tangibleaspects with 57.1% of dissatisfied users, followed by the dimension of responsiveness of health serviceswith 55.5% of dissatisfaction. Conclusions: the health system must implement strategies to improvecare services to provide timely and quality care to users.